Pengaruh Pembiayaan Musyarakah dan Tabungan Mudharabah terhadap Pendapatan Bagi Hasil - puji astuti, fitri (Jurnal Akuntansi UMMI, 2022)
This study aims to determine the extent to which the level of musyarakah financing, mudharabah savings on profit-sharing income in Islamic banking companies located at Bank Muamalat Sukabumi period . This study uses a quantitative approach in the form of numbers and the data used are secondary data. The sample in this study is customer data per month for 4 banking years registered at Bank Muamalat Sukabumi. Based on the results of the study, it shows that the partial test of independent musyarakah financing has no effect and the sig value is 0.002 and mudharabah savings has no effect with a sig value of 0.000. Based on the results of this f test, it shows that the f count is 59.393 and the f table is 4.10, so the t count is smaller than the f table value. Thus, together, musyarakah financing and mudharabah savings have an effect on profit-sharing income, then the hypothesis Ho is rejected and Ha is accepted.